Core/shell structured ZnO@SiO2-TTIP composite nanoparticles as an effective catalyst for the synthesis of 2-substituted benzimidazoles and benzothiazoles. Issue 1 (1st January 2018) - Bahrami, Kiumars; Karami, Zahra
Abstract: ZnO@SiO2 -TTIP was synthesised as a novel heterogeneous catalyst and characterised by FT-IR, XRD, TEM, SEM and N2 adsorption-desorption. In this catalytic system, TTIP acts as a dopant agent for ZnO@SiO2 to decreases the recombination of photogenerated electron/hole pairs and improves the catalyst activity. The catalyst was successfully utilised for the synthesis of 2-substituted benzimidazoles and benzothiazoles from 1, 2-phenylenediamine and 2-aminothiophenol with wide variety of aromatic aldehydes.